2019 Marriage Law Triggered “Baby Bust'” An Islamic Legal Perspective On The Decline In Marriage Rates - Yulizain Putra; Elfia; Zulfan (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2025)
The Marriage Law No. 1 of 2019 in Indonesia has sparked debates on its potential to trigger a